Analysis of Borderline Oxacillin-Resistant Staphylococcus aureus (BORSA) Strains Isolated in Tunisia - Maalej, Senda Mezghani (American Society for Microbiology, 2012)
Twenty-three strains of Staphylococcus aureus with borderline resistance to oxacillin were studied. These strains were not detected by the cefoxitin test, tests for penicillin-binding protein 2a (PBP2a), mecA, and mecA(LGA251) were negative, and the strains were genetically unrelated. To detect all strains resistant to oxacillin, laboratories should routinely test for both cefoxitin and oxacillin.